Selection of Staphylococcus aureus in a murine nasopharyngeal colonization model - Salgado, Breno A. B.; Waters, Elaine M.; Moran, Josephine C.; Kadioglu, Aras; Horsburgh, Malcolm J. (Frontiers in Cellular and Infection Microbiology, 2022)
Staphylococcus aureus nasal colonization is a risk factor for infection. A large proportion of the population are identified as potential S. aureus carriers yet we only partially understand the repertoire of genetic factors that promote long-term nasal colonization. Here we present a murine model of nasopharyngeal colonization that requires a low S. aureus inoculum and is amenable to experimental evolution approaches. We used this model to experimentally evolve S. aureus using successive passages in the nasopharynx to identify those genetic loci under selection. After 3 cycles of colonization, mutations were identified in mannitol, sorbitol, arginine, nitrite and lactate metabolism genes promoting key pathways in nasal colonization. Stress responses were identified as being under selective pressure, with mutations in DNA repair genes including dnaJ and recF and key stress response genes clpL, rpoB and ahpF. Peptidoglycan synthesis pathway genes also revealed mutations indicating potential selection for alteration of the cell surface. The murine model used here is versatile to question colonization, persistence and evolution studies.